Reasons for failure to perform interventional pain procedures in cancer patients: an analysis of pain clinic consultations. Issue 11 (November 2020) - Kim, Ki Wook; Kim, Shin Hyung; Won, Ji Yeon; Jang, Hun; Park, Sang Jun
Background: Interventional pain procedures (IPPs) may be necessary for some cancer patients when conservative treatment fails. However, many IPPs are often delayed or cancelled for cancer patients who are referred to the pain clinic. Methods: We retrospectively analyzed the reasons for such cancellations to identify clinically avoidable causes of the delay in IPP. Results: We enrolled 350 cancer patients who were referred to our pain clinic for an IPP between March 2016 and February 2018. There were 213 (60.9%) cases that were cancelled, among which 115 (54%) cases were potentially avoidable and 98 (46%) were unavoidable. The most common reasons for cancellation were patient-derived factors, which accounted for 85 (39.9%) cases. Patient refusal was a common reason for cancellation, with 33 (15.5%) cases attributed to this cause. The primary avoidable causes of cancellation were a recommendation that the patient continue with their current pharmacological pain treatment, conflict with another planned treatment, and pain characteristics that were not suitable for an IPP. Together, these accounted for 76.5% of all avoidable cancellations. Conclusions: Comprehensive and accurate pain assessments before IPP may result in more favorable outcomes for the efficient use of medical resource and effective pain relief in cancer patients.